Quality of strawberries subjected to pre-harvest UV-C radiation - Nardello, Izabel Camacho; Cantillano, Rufino Fernando Flores; Ribeiro, Jardel Araújo; Vignolo, Gerson Kleinick; Malgarim, Marcelo Barbosa; Mello-Farias, Paulo Celso de (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the influence of the use of UV-C radiation at an intensity of 0.53 KJ m-2, during strawberry (Fragaria x ananassa) cultivation, on the physicochemical and phytochemical parameters of the fruits. The used experimental design was completely randomized, in a single-factor arrangement with 11, 19, 29, and 39 UV-C applications and without UV-C application. The hue of the fruits was smaller at the end of the study period. pH varied in strawberries that received 39 applications of UV-C, and the soluble solids content differed with 19 applications. Antioxidant activity was lower in fruits with 11, 19, and 29 UV-C applications, whereas vitamin C content was lower only in fruits that received 29 applications. The use of UV-C radiation at an intensity of 0.53 KJ m-2, during strawberry cultivation, affects the physicochemical and phytochemical parameters of the fruits, but does not cause losses in their quality.